1996
DOI: 10.1002/(sici)1097-0215(19960126)65:3<323::aid-ijc8>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and subcellular localisation of cyclin D3 in human tumours

Abstract: The D-type cyclins are positive regulators of the GI phase of the mammalian cell cycle. Cyclins D I or D2 are over-expressed in several types of cancer, transform rodent cells in culture and therefore harbor hallmarks of cellular proto-oncogenes. In contrast, no data on expression of cyclin 0 3 in tissues and tumours are presently available. We have raised monoclonal antibodies (MAbs) specific for cyclin D3 and examined abundance and subcellular localisation of this GI cyclin in a series of human cultured cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 18 publications
6
39
0
Order By: Relevance
“…Northern blot analysis of transcripts encoding the D-type cyclins showed that cyclin D3 transcripts were also the most abundant in the thyroids of control mice (Figure 3a). Immunohistochemistry (IHC) performed on thyroid tissue sections, revealed a nuclear localization of cyclin D3 but the staining appeared heterogeneous in intensity, as previously reported for cyclin D3 and other cyclin D subtypes in various normal and tumoral human tissues (Bartkova et al, 1996). About 23.3+3.5 (mean+s.d.…”
Section: Expression Of Cyclins and Cdkssupporting
confidence: 69%
See 1 more Smart Citation
“…Northern blot analysis of transcripts encoding the D-type cyclins showed that cyclin D3 transcripts were also the most abundant in the thyroids of control mice (Figure 3a). Immunohistochemistry (IHC) performed on thyroid tissue sections, revealed a nuclear localization of cyclin D3 but the staining appeared heterogeneous in intensity, as previously reported for cyclin D3 and other cyclin D subtypes in various normal and tumoral human tissues (Bartkova et al, 1996). About 23.3+3.5 (mean+s.d.…”
Section: Expression Of Cyclins and Cdkssupporting
confidence: 69%
“…The antibodies used in this study were the mouse monoclonals DCS 6 (Lukas et al, 1994b), DCS 3.1 (Lukas et al, 1995b) and DCS 22 (Bartkova, 1996) respectively directed against human cyclin D1, D2 and D3; the mouse monoclonals DCS 31, DCS 32 and DCS 35 directed against human cdk4 (Bartek et al, manuscript in preparation); and the polyclonal rabbit serum against bovine thyroglobulin (Roger et al, 1985). Polyclonal rabbit sera raised against human cdk2 (M-2), rat cyclin E (M-20), mouse cyclin A (C-19) and human p27 kip1 (C-19), as well as the anti-human cdc2 mouse monoclonal (17) were purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA).…”
Section: Antibodiesmentioning
confidence: 99%
“…Of these, increased expression of cyclins A, B, D and E have been reported in breast tumors or carcinoma cell lines (Buckley et al, 1993;Keyomarso and Pardee, 1993;Dutta et al, 1995;Keyomarsi et al, 1995). Within the cyclin D family, overexpression and/or ampli®cation of cyclin D1 (Gillett et al, 1994;Zhang et al, 1994;Zuckerberg et al, 1995;Courjal et al, 1996;Michalides et al, 1996) and D3 (Bartkova et al, 1996) have been reported in cohorts of invasive breast carcinomas; increased cyclin D1 expression was correlated with the presence of estrogen receptors. Both cyclin D1 transgenic mouse data (Wang et al, 1994) and transfection experiments using the human T-47D breast carcinoma cell line supported the hypothesis that cyclin D1 may be a breast cancer oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…Cells with widespread alterations undergo apoptosis (Harbour and Dean, 2000). Different defects affecting the regulation of the G1/S transition have been detected in various malignancies (Bartkova et al, 1996;Gillet et al, 1996;Hommura et al, 2000;Kawauchi et al, 2001). This suggests that cell cycle aberrations probably represent one of a limited number of key events in the transformation process (Hahn et al, 1999).…”
mentioning
confidence: 99%